The metabolic effect of Momordica charantia cannot be determined based on the available clinical evidence: a systematic review and meta-analysis of randomized clinical trials - Laczkó-Zöld, Eszter; Csupor-Löffler, Boglárka; Kolcsár, Edina-Blanka; Ferenci, Tamás; Nan, Monica; Tóth, Barbara; Csupor, Dezső (Frontiers in Nutrition, 2024)
Several studies have shown that Momordica charantia L. (Cucurbitaceae, bitter melon) has beneficial effects on metabolic syndrome (MetS) parameters and exerts antidiabetic, anti-hyperlipidemic, and anti-obesity activities. Since the findings of these studies are contradictory, the goal of this systematic review and meta-analysis was to assess the efficacy of bitter melon in the treatment of metabolic syndrome, with special emphasis on the anti-diabetic effect. Embase, Cochrane, PubMed, and Web of Science databases were searched for randomized controlled human trials (RCTs). The meta-analysis was reported according to the PRISMA statement. The primary outcomes of the review are body weight, BMI, fasting blood glucose, glycated hemoglobin A1c, systolic blood pressure, diastolic blood pressure, serum triglyceride, HDL, LDL, and total cholesterol levels. Nine studies were included in the meta-analysis with 414 patients in total and 4–16 weeks of follow-up. In case of the meta-analysis of change scores, no significant effect could be observed for bitter melon treatment over placebo on fasting blood glucose level (MD = -0.03; 95% CI: -0.38 to 0.31; I2 = 34%), HbA1c level (MD = -0.12; 95% CI: -0.35 to 0.11; I2 = 56%), HDL (MD = -0.04; 95% CI: -0.17 to 0.09; I2 = 66%), LDL (MD = -0.10; 95% CI: -0.28 to 0.08; I2 = 37%), total cholesterol (MD = -0.04; 95% CI: -0.17 to 0.09; I2 = 66%,), body weight (MD = -1.00; 95% CI: -2.59–0.59; I2 = 97%), BMI (MD = -0.42; 95% CI: -0.99–0.14; I2 = 95%), systolic blood pressure (MD = 1.01; 95% CI: -1.07–3.09; I2 = 0%) and diastolic blood pressure levels (MD = 0.24; 95% CI: -1.04–1.53; I2 = 0%). Momordica treatment was not associated with a notable change in ALT, AST, and creatinine levels compared to the placebo, which supports the safety of this plant. However, the power was overall low and the meta-analyzed studies were also too short to reliably detect long-term metabolic effects. This highlights the need for additional research into this plant in carefully planned clinical trials of longer duration.